1997
DOI: 10.1002/pro.5560060206
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protein structure in intact cells: Crosslinking in vivo between introduced cysteines in the transmembrane domain of a bacterial chemoreceptor

Abstract: Oxidative crosslinking of cysteines introduced by site-specific mutagenesis is a powerful tool for structural analysis of proteins, but the approach has been limited to studies in vitro. We recently reported that intact cells of Escherichia coli could be treated with Cu(II)-(o-phenanthroline)3 or molecular iodine in a way that left unperturbed flagellar function or general chemotactic response, yet crosslinks were quantitatively formed between select cysteines in adjoining transmembrane helices of chemorecepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
69
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 34 publications
2
69
0
Order By: Relevance
“…3). This indiscriminate cross-linking is reminiscent of findings with other protein complexes after prolonged exposure to CuP and has been attributed to rotational mobility or flexibility of the protein backbone (25,26). In contrast, the increase in cross-linking in the C-terminal half of TM1 was relatively selective for positions 98, 101, and 105, reinforcing the evidence of a helical repeat, and the fractional cross-linking at residues 99, 100, 103, and 104 remained very low (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…3). This indiscriminate cross-linking is reminiscent of findings with other protein complexes after prolonged exposure to CuP and has been attributed to rotational mobility or flexibility of the protein backbone (25,26). In contrast, the increase in cross-linking in the C-terminal half of TM1 was relatively selective for positions 98, 101, and 105, reinforcing the evidence of a helical repeat, and the fractional cross-linking at residues 99, 100, 103, and 104 remained very low (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…The mechanism of transmembrane signaling is a subtle piston-type displacement of the signaling helix ␣4/TM2 toward the cytoplasm, as observed in the superimposed crystal structures of the apo-and aspartate-occupied periplasmic domain (43). Further evidence for the piston displacement is provided by engineered disulfide bonds that lock the membrane-bound receptor in the on and off states, by ligand-induced changes in disulfide formation rates detected in a closely related receptor for ribose and galactose, and, most recently, by spin-labeled ESR measurements (34,39,(43)(44)(45).…”
mentioning
confidence: 83%
“…Attractant binding to the receptor generates a piston (or swinging-piston) displacement of the signaling helix toward the cytoplasm (40). Parallel studies have shown that the related chemoreceptor for ribose and galactose shares the same helical structure and piston-type signaling mechanism, illustrating the generality of this transmembrane signaling motif at least within the bacterial chemoreceptor subfamily of two-transmembrane helix receptors (41)(42)(43)(44)(45)(46).…”
mentioning
confidence: 98%